Matrix methods of structural analysis - Wang, Chu-Kia (International Textbook Co., 1966)
Matrix Methods of Structural Analysis is a highly specialized subject requires an excellent understanding of the fundamentals and special methods of analysis of various structures. This book is a comprehensive presentation of the fundamental aspects of matrix analysis of structures. It reflects many of the problems and queries the students have in understanding the basics of matrix representation and analysis.